The Growth Performance of Tilapia (Oreochromis niloticus) Seeds Fed with Different Quantities of a Synbiont Feed - Rahmi Rahmi; Andi Ninnong Renita Relatami; Akmal Akmal; Sri Wahyuni Firman; Bunga Rante Tampangallo; Andi Chadijah; Dida Ardiayana (Universitas Gadjah Mada, 2021)
This study were aims to test the growth performance of tilapia (Oreochromis niloticus) seeds fed with different quantities of the symbiont, consisting of a probiotic and a prebiotic, such as B. subtilis and banana flour, respectively. This study employs an experimental approach with a completely randomized design (CRD). Furthermore, artificial feeds were prepared as various treatments, consisting of B. subtilis and banana flour concentrations. They include treatment A, which does not contain B. subtilis and banana flour, and also treatment B, C, and D, which consists of B. subtilis at concentrations of 105 CFU/mL, 107 CFU/mL, and 109 CFU/mL, respectively, as well as 1% banana flour. The results obtained showed that weight gain (WG) and specific growth rate SGR were significantly different in treatment B but the survival rate (SR), food conversion rasio (FCR), hepatosomatic index (HSI), and condition factor (K) did not show significant results. Meanwhile, somatic digestive index (DSI) showed a significant difference with treatment A, C, and D, but not with treatment B. However, treatment B showed a relatively better performance based on the SR, FCR, and WG at 96.67 %, 1.05 %, and 3.49 %, respectively.